Symmetry-dependent exciton-exciton interaction and intervalley biexciton in monolayer transition metal dichalcogenides - Hoang Ngoc Cam; Nguyen Thanh Phuc; Vladimir A. Osipov (npj 2D Materials and Applications, 2022)
Abstract The multivalley band structure of monolayer transition metal dichalcogenides (TMDs) gives rise to intravalley and intervalley excitons. Much knowledge of these excitons has been gained, but fundamental questions remain, such as how to describe them all in a unified picture with their correlations, how are those from different valleys coupled to form the intervalley biexciton? To address the issues, we derive an exciton Hamiltonian from interpair correlations between the constituent carriers-fermions of two excitons. Identifying excitons by irreducible representations of their point symmetry group, we find their pairwise interaction depending on interacting excitons’ symmetry. It is generally repulsive, except for the case excitons from different valleys, which attract each other to form the intervalley biexciton. We establish a semianalytical relationship between the biexciton binding energy with exciton mass and dielectric characteristics of the material and surroundings. Overall, by providing insight into the nature of diverse excitons and their correlations, our theoretical model captures the exciton interaction properties permitting an inclusive description of the structure and energy features of the intervalley biexciton in monolayer TMDs.